Intense Current Structures Observed at Electron Kinetic Scales in the Near‐Earth Magnetotail During Dipolarization and Substorm Current Wedge Formation. Issue 2 (31st January 2018) - Grigorenko, E. E.; Dubyagin, S.; Malykhin, A. Yu.; Khotyaintsev, Yu V.; Kronberg, E. A.; Lavraud, B.; Ganushkina, N. Yu
Abstract: We use data from the 2013–2014 Cluster Inner Magnetosphere Campaign, with its uniquely small spacecraft separations (less than or equal to electron inertia length, λ e ), to study multiscale magnetic structures in 14 substorm‐related prolonged dipolarizations in the near‐Earth magnetotail. Three time scales of dipolarization are identified: (i) a prolonged growth of the B Z component with duration ≤20 min; (ii) B Z pulses with durations ≤1 min during the B Z growth; and (iii) strong magnetic field gradients with durations ≤2 s during the dipolarization growth. The values of these gradients observed at electron scales are several dozen times larger than the corresponding values of magnetic gradients simultaneously detected at ion scales. These nonlinear features in magnetic field gradients denote the formation of intense and localized (approximately a few λ e ) current structures during the dipolarization and substorm current wedge formation. These observations highlight the importance of electron scale processes in the formation of a 3‐D substorm current system. Key Points: Multiscale current structure formed during dipolarization growth Intense current structures are transiently (≤2 s) observed at the leading and trailing edges of B Z pulses during dipolarization growth Spatial scales of the intense current structures are 100–200 km (2.5–5.0)λ e